THE IMPLEMENTATION OF EDUCATIONAL TECHNOLOGY IN LEARNING PROCESS - RINA OKTAFIA PUTRI (Sriwijaya University Learning and Education International Conference, 2016)
Science is a human endeavor to understand the symptoms and the facts of nature, and preserves such knowledge conceptually and systematically. While the technology is man's attempt to take advantage of that knowledge for the benefit and well-being. Educational technology is designed to solve the problems of education, as well as to provide the benefit in improving the quality of learning process. Various forms of learning experience, both of which can be accomplished either in the classroom or outside the classroom, and messages can be packaged by observing the rules and principles of educational technology. The new paradigm of education favor of the election of the quality of education with emphasis on the principles and practice of autonomy, accountability, accreditation and evaluation to achieve such quality with no other implements appropriate educational technology. Educational technology as a form of software (software technology) in the form of systematic ways is used to solve the problem of increasingly sophisticated learning process and get a place widely in education. Thus, the practical implementation of educational technology in problem solving learning process that has a concrete form with the learning resources that facilitate learners to learn.